The Christian valuation and significance of suffering according to Vatican Council II, and the five basic psychic needs of man posited by Erich Fromm: An interdisciplinary study - Simmons, Henry Carl (University of Ottawa (Canada), 1970)
Abstract not available.
Keywords: Theology.; Psychology, General.